The Phyllotis xanthopygus complex (Rodentia, Cricetidae) in central Andes, systematics and description of a new species - Jayat, Jorge Pablo (2021)
Fil: Jayat, Jorge Pablo. Consejo Nacional de Investigaciones Científicas y Técnicas. Centro Científico Tecnológico (Tucumán). Unidad Ejecutora Lillo; Argentina